(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Tinnitus is one of the annoying disorders which can significantly impair patient’s quality of life and productivity. Although it is not a life threatening disease, but it results into emotional distress, cognitive distress, intrusiveness, auditory and perceptual difficulties, sleep disturbances, and various somatic complaints. Its incidence and prevalence are enhancing day by day. Various pharmacological agents including anticonvulsants, anxiolytics, antidepressants, muscle relaxants etc. are presently used or trialed for its pacification, but there is little evidence of their benefit over harm. The role of invasive and non-invasive Neurostimulation treatments, supposed to be very effective, are also little known. The introduction of Hearing aids and cochlear implantation are also not very much conclusive. No evidence of a significant change in the subjective loudness of tinnitus has been noticed with Cognitive behavioural treatment. In this way, there is a need for making an availability of uniformly accepted, broadly effective treatments capable of drastically decreasing the loudness and impact of tinnitus and withstanding systematic replication. This article is for serving the very purpose. Here, an effort has been made to present the remedial procedures and regimen for the alleviation of tinnitus described in Ayurveda, an ancient healing science of India. In Ayurveda, tinnitus has been delineated in the name of Karnanada. The article also brings about several case studies and clinical studies on tinnitus carried out at different centres/Institutes of Ayurveda.